Quasiclassical Theory of C4-Symmetric Magnetic Order in Disordered Multiband Metals - Dzero, Maxim; Khodas, Maxim (Frontiers in Physics, 2020)
Recent experimental studies performed in the normal state of iron-based superconductors have discovered the existence of the C4-symmetric (tetragonal) itinerant magnetic state. This state can be described as a spin density wave with two distinct magnetic vectors Q1 and Q2. Given an itinerant nature of magnetism in iron-pnictides, we develop a quasiclassical theory of tetragonal magnetic order in disordered three-band metal with anisotropic band structure. Within our model, we find that the C4-symmetric magnetism competes with the C2-symmetric state with a single Q magnetic structure vector. Our main results are that disorder promotes a tetragonal magnetic state which is in agreement with earlier theoretical studies.